Social Capital As A Factor Of Sustainable Development Of New Uzbekistan - Norkuziyev Sodikjon Khakimovich (Periodica Journal, 2026)
The fact that the world we live in today aims to build a society based on human potential is, to some extent, bringing about changes in society by studying some aspects of social capital. Social capital is an indicator of the cultural level of society, an important tool in creating the basis of civil society. It develops by embodying moral standards, knowledge, skills and abilities of people. Currently, quality education, qualified medical care, stable functioning of the principles of justice and the rule of law, and the free functioning of social institutions are the main signs of a social state, developing social capital as one of the state models aimed at ensuring the strength of the social protection system, ensuring employment, creating safe working conditions, and reducing poverty.
Keywords: Welfare state; social capital; co-determination